Analysis of Agricultural Zakat Payment System in Pengadangan Village, Lombok Timur Regency - Ainul Hijji; Totona , Saiful; Busaini, Busaini; Rashed Jahangir; Jahid Hasan Rony; Doktoralina , Caturida Meiwanto (Journal of Social and Humanities, 2024)
The purpose of this study was to determine the agricultural zakat payment system by farmers in Pengadangan village, Pringgasela sub-district, East Lombok district. The approach used in this research is a qualitative approach using descriptive methods. Data collection techniques in this study are using field observations, interviews, and documentation. Determination of informants in this study was purposive and snowball. The informants in this study occurred from 6 informants, 1 key informant, 3 main informants and 2 additional informants. Data validity uses source tringulation, method tringulation, theory tringulation. Data analysis in the form of data reduction, data display (presentation of data), conclusion drawing (verification). From the six informants, it can be concluded that the agricultural zakat payment system by farmers in Pengadangan Village, Peringgesela sub-district, Lombok Timur district. In the payment of informants already understand about agricultural zakat starting from the nisab, the pillars and conditions of zakat, as well as the distribution (Year). Of the six informants studied regarding the zakat payment system such as the time of issuing zakat, the level of zakat issued and the distribution of the age (year) is in accordance with the Qur'an, Hadith, and Ijma Ulama. Farmers pay agricultural zakat at 10% if they use rainwater and 5% if they use irrigation. When viewed from the perspective of maqashid sharia, the six informants studied have been able to fulfill the needs of daruryyat, hajiyyat, and tahsiniyyat such as protecting religion, soul, mind, offspring and property.